An in Vitro Approach: Antibacterial Activity of Sansevieria trifasciata Prain. Leaves with Chemometric Analysis - Kasmawati, Henny; Sida, Nurramadhani A.; Arfan, Arfan; Indrayanti, Wa Ode Dian; Rusman, Arman (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Exploration the antibacterial activity of S.trifasciata Prain. is still limited, therefore this study aims to assess the antibacterial activity of extracts and ethyl acetate fractions of Sansevieria trifasciata Prain. The S.trifasciata leaves was macerated with ethanol 96%, then fractionated using the trituration method with ethyl acetate. The treatment group was divided into positive control group (PC) using ciprofloxacin, negative control (NC) using DMSO, extract, ethyl acetate fraction 5% (ET5%), 10% (ET10%), 20% (ET20%), 40% (ET40 %). Data were analyzed statistically by ANOVA and chemometrically with PCA. The inhibition zone for S.aureus bacteria in each sample is 26.69; 1.40; 23.32;2.82; 6.23; 11.11; 20.15 mm, respectively, E.coli is 26.65;0.63;22.65;3.61;7.11;11.44;21.15 mm respectively, P. aeruginosa is 27.40; 0.00; 23.23; 2.74;7.03;11.69;21.36 mm respectively. Percent inhibition of extract, ET5%, ET10%, ET20%, ET40% on S. aureus bacteria is 82.16; 5.31; 18.12; 36.39; 70.38% respectively, E.coli is 82.67; 11.13; 24.31; 40.56; 76.99% respectively, P. aeruginosa 84.85; 10.01; 25.65; 42.68; 77.98% respectively. Extract and ethyl acetate fraction have significant potential as antibacterial (p<0.05). The results of PCA chemometric analysis showed that the extract and ET40% had similar inhibition zone area to the positive control ciprofloxacin. The extract and the ethyl acetate fraction 40% are promising for development as antibacterials. Keywords: Sansevieria trifasciata Prain., chemometric, bacterial